O regime brasileiro de tributação de lucros auferidos por sociedades controladas e coligadas no exterior: uma visão do atual regime por meio da ótica da teoria do rent seeking - Hirata, Dalton Yoshio (2012)
This work intends to analyze, from the perspective of the 'rent seeking' theory, the historical evolution of the legislation and case law about the tax on profits, capital gains and income earned by corporations established abroad. The hypothesis is that this legislation and its many interpretations reflect rent seeking interests by both some government sectors as well as the private sector. Accordingly, the theory of rent seeking is analyzed and its relation to the theory of 'patrimonialismo' in Brazil is demonstrated. Afterwards, the theory is applied to the proposed tax theme. To reach this objective, this work analyzes the evolution of the legislation until the last relevant law: Provisional Measure No. 2158-35 / 01. The main controversies will be identified as well as possible economic (rent seeking) interests in the various interpretations of the rules in question. Afterwards, this works verifies in the decisions of the Superior Court of Justice (STJ), the Supreme Federal Court (STF) and the Administrative Tax Court (CARF) the evolution of courts’ understanding about the various interpretations. It will be analyzed if any consensus could be obtained and which economic interests would be affected by the course taken by the case law on the theme. In this context, the analysis of legislative and jurisprudential evolution will address the following controversial issues: (1) characterization of the Brazilian rules as CFC rules (antiavoidance feature), (2) taxation of a deemed profit distribution or of the own Brazilian company profits; (3) the constitutionality of Article 43, paragraph 2, of the National Tax Code, and Article 74 of the Provisional Measure No. 2158-35/01; and (4) the compatibility of this regime with the Treaties on Double Taxation. Finally, a conclusion will be made from the findings, regarding how the changing tax rules in question may represent a rent seeking situation without public benefits that may unduly benefit both the public and the private sectors.